An improvement in creep strength of thermo-mechanical treated modified 9Cr-1Mo steel weld joint. (2nd January 2019) - Sakthivel, T.; Nandeswarudu, S. M.; Shruti, P.; Nageswara Rao, G. V. S.; Laha, K.; Sasikala, G.; Srinivasa Rao, T.
Abstract: Modified 9Cr-1Mo steel weld joints generally experience the type IV premature failure in the intercritical region (ICR) of HAZ under long term creep exposure at high temperature. Possibility of improving the resistance of this joint to type IV cracking through thermo-mechanical treatment (TMT) of the steel has been explored. Weld joints have been fabricated from the TMT and conventional normalized and tempered (NT) steels using electron beam (EB) welding process. Creep tests have been carried out on NT and TMT steels joint at 923 K (650°C) and 110–100 MPa applied stress. Creep rupture life of the TMT weld joint was significantly higher than the NT steel weld joint. Significant variations of microstructural constituents such as M23 C6 precipitate; lath structure and hardness across the joint have been examined in both the joints. The coarser M23 C6 precipitate and lath, and subgrain formation in the ICR resulted in the soft zone formation and was predominant in the ICR of NT steel joint. The enhanced MX precipitation through TMT processing and reduction in coarsening of M23 C6 precipitate under thermal cycle resulted in improved creep rupture strength of TMT steel weld joint.